Is low-input dairy farming more climate friendly? A meta-analysis of the carbon footprints of different production systems. (20th February 2019) - Lorenz, Heike; Reinsch, Thorsten; Hess, Sebastian; Taube, Friedhelm
Abstract: The global warming potential of milk production is a key aspect in the assessment of its eco-efficiency. The carbon footprint summarises the climate-relevant emissions of the production cycle, with this study focussing on the emissions from cradle to farm gate as boundaries. Numerous life cycle assessments were published in recent years, presenting the carbon footprint for different regions, production systems and management scenarios. However, despite the obvious high scientific interest in this topic, general conclusions on the climate-friendliness of contrasting production systems can hardly be drawn and there is no clear answer to the question of whether or not grazing systems provide an overall more climate-friendly alternative to confinement systems. To resolve this discussion, a meta-analysis was applied to a dataset, created with data from a selection of 30 published life cycle assessments, comprising in total 87 carbon footprint values from 15 different countries. After a standardisation process, three production system categories (pasture-based, mixed and confinement) were defined based on feeding parameters. Aside from the comparison of the production systems, the effects of various production variables (pasture and concentrate intake, milk yield per cow, milk yield per kg of metabolic live weight, mineral nitrogen fertilisation, feed efficiency and replacement rate) were analysed. Therefore, linear and level-log mixed models were developed and analyses of covariance performed. As the dataset used for the analysis covered a large range of different intensities per production system, the results are based on a robust analysis and can be extrapolated to any milk production system with known in- and outputs. The results show that increases in milk yield, pasture intake and feed efficiency decreased the carbon footprint of milk significantly, independent of the production system. However, the mitigation potential is limited across production systems with regard to their productivity thresholds. The comparison of the systems without consideration of other production parameters did not reveal any significant differences. When controlling for milk yield, however, the pasture-based system achieved lower carbon footprints compared to the other production systems. Thus, irrespective of the importance of milk yield for emissions and the generally lower milk yields of the pasture-based production system, this system still offers a competitive climate impact. Highlights: Meta-analysis of 30 published life cycle assessments. Comparison of three different milk production systems. Reduction of methodological discrepancies between studies. Production parameters have an effect on the carbon footprint. Pasture systems can compete despite low milk yields.